An Investigative Study of Quantum-safe Secure Multi-party Computation - Aiswarya Dwarampudi; Yamuna Mundru; Manas Kumar Yogi (International Journal of Computer Science Languages, 2024)
This article represents the comprehensive investigation in the emerging field of quantum-safe secure multi-party computation (QSSMPC) and presents novel perspectives to address the impending threat posed by quantum computers to classical cryptographic systems. As the era of quantum computing approaches, traditional encryption methods become vulnerable to quantum algorithms, necessitating the development of quantum-resistant cryptographic protocols. In this context, the paper introduces innovative approaches to secure multi-party computation in a quantum-safe framework. It discusses the theoretical foundations of quantum-safe cryptography and its integration into multi-party computation protocols. The paper also explores practical implementations and potential applications of QSSMPC in real-world scenarios, emphasizing the importance of transitioning towards quantum-resistant cryptographic techniques to ensure the long-term security of sensitive data. The provided viewpoints seek to actively engage in the ongoing discussion surrounding quantum-safe cryptographic systems, providing valuable perspectives that guide the creation of resilient and secure computing frameworks in the post-quantum era.
Keywords: Encryption; Privacy; private key; quantum; secure multi-party computation (SMPC); security